Effect of Tocilizumab vs Standard Care on Clinical Worsening in Patients Hospitalized With COVID-19 Pneumonia: A Randomized Clinical Trial - Salvarani, Carlo (JAMA Intern Med, 2021)
IMPORTANCE: The coronavirus disease 2019 (COVID-19) pandemic is threatening billions of people worldwide. Tocilizumab has shown promising results in retrospective studies in patients with COVID-19 pneumonia with a good safety profile. OBJECTIVE: To evaluate the effect of early tocilizumab administration vs standard therapy in preventing clinical worsening in patients hospitalized with COVID-19 pneumonia. DESIGN, SETTING, AND PARTICIPANTS: Prospective, open-label, randomized clinical trial that randomized patients hospitalized between March 31 and June 11, 2020, with COVID-19 pneumonia to receive tocilizumab or standard of care in 24 hospitals in Italy. Cases of COVID-19 were confirmed by polymerase chain reaction method with nasopharyngeal swab. Eligibility criteria included COVID-19 pneumonia documented by radiologic imaging, partial pressure of arterial oxygen to fraction of inspired oxygen (Pao(2)/Fio(2)) ratio between 200 and 300 mm Hg, and an inflammatory phenotype defined by fever and elevated C-reactive protein. INTERVENTIONS: Patients in the experimental arm received intravenous tocilizumab within 8 hours from randomization (8 mg/kg up to a maximum of 800 mg), followed by a second dose after 12 hours. Patients in the control arm received supportive care following the protocols of each clinical center until clinical worsening and then could receive tocilizumab as a rescue therapy. MAIN OUTCOME AND MEASURES: The primary composite outcome was defined as entry into the intensive care unit with invasive mechanical ventilation, death from all causes, or clinical aggravation documented by the finding of a Pao(2)/Fio(2) ratio less than 150 mm Hg, whichever came first. RESULTS: A total of 126 patients were randomized (60 to the tocilizumab group; 66 to the control group). The median (interquartile range) age was 60.0 (53.0-72.0) years, and the majority of patients were male (77 of 126, 61.1%). Three patients withdrew from the study, leaving 123 patients available for the intention-to-treat analyses. Seventeen patients of 60 (28.3%) in the tocilizumab arm and 17 of 63 (27.0%) in the standard care group showed clinical worsening within 14 days since randomization (rate ratio, 1.05; 95% CI, 0.59-1.86). Two patients in the experimental group and 1 in the control group died before 30 days from randomization, and 6 and 5 patients were intubated in the 2 groups, respectively. The trial was prematurely interrupted after an interim analysis for futility. CONCLUSIONS AND RELEVANCE: In this randomized clinical trial of hospitalized adult patients with COVID-19 pneumonia and Pao(2)/Fio(2) ratio between 200 and 300 mm Hg who received tocilizumab, no benefit on disease progression was observed compared with standard care. Further blinded, placebo-controlled randomized clinical trials are needed to confirm the results and to evaluate possible applications of tocilizumab in different stages of the disease. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04346355; EudraCT Identifier: 2020-001386-37